Web Modelling for Web Warehouse Design - Gomes, Daniel (2007)
Users require applications to help them obtaining knowledge from the web. However, the specific characteristics of web data make it difficult to create these applications. One possible solution to facilitate this task is to extract information from the web, transform and load it to a Web Warehouse, which provides uniform access methods for automatic processing of the data. Web Warehousing is conceptually similar to Data Warehousing approaches used to integrate relational information from databases. However, the structure of the web is very dynamic and cannot be controlled by the Warehouse designers. Web models frequently do not reflect the current state of the web. Thus, Web Warehouses must be redesigned at a late stage of development. These changes have high costs and may jeopardize entire projects. This thesis addresses the problem of modelling the web and its influence in the design of Web Warehouses. A model of a web portion was derived and based on it, a Web Warehouse prototype was designed. The prototype was validated in several real-usage scenarios. The obtained results show that web modelling is a fundamental step of the web data integration process